Mobility and rights in the Portuguese-speaking World: A lusophone citizenship in bits and pieces - Jerónimo, Patrícia (2021)
Enhanced international mobility has been a goal of the Community of Portuguese Language Countries (CPLP) since its inception in 1996 and is often discussed in tandem with the topic of a ‘Lusophone citizenship’. While the projects to establish a separate citizenship status at CPLP level did not yet come to fruition, there have been important legal developments over the years and there is a considerable number of ways in which mobility and rights are accessible to member states’ nationals in the CPLP area, under multilateral or bilateral agreements and domestic provisions. The paper pieces together the statuses (formally) enjoyed by member states’ nationals when moving in the CPLP area and compares the content of those statuses to that which is expected from Lusophone citizenship, as indicated in draft treaties, policy documents and academic debates on the topic. For context, the analysis is preceded by a brief look into CPLP history and the origins of the concept of Lusophone citizenship.